2023
DOI: 10.1101/2023.11.01.565056
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incorporation of 5 methylcytidine alleviates innate immune response to self-amplifying RNA vaccine

Mai Komori,
Amber L. Morey,
Andrés A. Quiñones-Molina
et al.

Abstract: In order to improve vaccine effectiveness and safety profile of existing synthetic RNA-based vaccines, we have developed a self-amplifying RNA (saRNA)-based vaccine expressing membrane-anchored receptor binding domain (RBD) of SARS-CoV-2 S protein (S-RBD) and have demonstrated that a minimal dose of this saRNA vaccine elicits robust immune responses. Results from a recent clinical trial with 5-methylcytidine (5mC) incorporating saRNA vaccine demonstrated reduced vaccine-induced adverse effects while maintainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…But this was an assumption that had not been tested due to the fact that saRNA does not tolerate the incorporation of the most commonly modified nucleotides used in conventional mRNAs, such as pseudouridine. However, this scenario has recently changed with the discovery that saRNA can be modified with certain nucleotides, like 5-mC, and that these modifications improve the performance of these vectors [ 93 , 94 ]. Remarkably, one of these modified saRNAs has already been tested in a phase I clinical trial in Japan with promising results [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But this was an assumption that had not been tested due to the fact that saRNA does not tolerate the incorporation of the most commonly modified nucleotides used in conventional mRNAs, such as pseudouridine. However, this scenario has recently changed with the discovery that saRNA can be modified with certain nucleotides, like 5-mC, and that these modifications improve the performance of these vectors [ 93 , 94 ]. Remarkably, one of these modified saRNAs has already been tested in a phase I clinical trial in Japan with promising results [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, it was believed that this was not feasible, since many groups had failed to modify saRNA with pseudouridine, the most common modification used in conventional mRNA vaccines. However, two recent reports showed that saRNA can be modified with other nucleotides, such as 5-hydroxymethylcytidine, 5-methylcytidine (5-mC), and 5-methyluridine [ 93 , 94 ]. These modifications led to a considerable reduction in IFN-I induction both in vitro and in vivo, resulting in a higher and more robust expression of transgenes compared to unmodified saRNA.…”
Section: Strategies To Increase Efficacy Of Sarna Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its low dose of only 5 µg probably reduced reactogenicity to such an extent that it became tolerable [ 4 , 5 ]. Encouragingly, a recent comprehensive test of a variety of modified nucleotides has shown that 5-methyl cytidine (5 mC) reduces the immunogenicity of saRNA without affecting its function [ 82 , 83 ], raising hopes for even less reactogenic saRNA in the future.…”
Section: Future Perspective Of Tarna Vaccines Challenges and Open Que...mentioning
confidence: 99%
“…Therefore, innate responses were minimized in VLPCOV-02 by incorporation of 5-MeC, an approach supported by both preclinical in vitro and animal model observations. 19 The resulting modified product, VLPCOV-02, is currently being studied as a booster vaccine in a clinical trial setting in Japan.…”
Section: Introductionmentioning
confidence: 99%